Interação entre líquidos iônicos imidazolíneos e os alginatos de sódio e hidroxâmico - Freitas, Darcson Vieira de (2019)
This work describes the interactions between sodium alginate (ALG) and hydroxamic alginate (AHX) with the monocationic imidazolium ionic liquids series (CnMIMBr). From the surface tension, electrical conductivity, isothermal titration calorimetry (ITC), surface plasmon resonance (SPR), zeta potential, rheology and atomic force microscopy (AFM) techniques, we evaluated the effect of the alkyl chain length (n = 10, 12, 14 and 16), the concentration of the ILs and the polyelectrolytes, the charge density of the polyelectrolytes, on the formation of complexes AHX/CnMIMBr and ALG/CnMIMBr. The critical aggregation concentrations (C1, C2, CS and Cm) and the thermodynamic parameters of micellization and aggregation were calculated by these techniques. It was observed that the interactions with AHX are favored by the increase in the alkyl chain length of IL, whereas the interactions with ALG were more favorable with the more hydrophilic ionic liquids. The increase in the concentration of polyelectrolytes disadvantage the formation of free micelles of ILs as consequence of their aggregation in the chains of AHX and ALG. From the different techniques, the aggregation processes were determined in different concentrations of CnMIMBr. At low concentrations, electrostatic interactions are predominant and, when the concentration of ILs is increased, hydrophobic and ion-dipole interactions become more pronounced. By dividing the aggregation processes into different IL concentration ranges, it was possible to experimentally determine several thermodynamic parameters of the interaction and micellization processes. The hydrophobic interaction is discussed in detail, in particular by the Kagg2 equilibrium constant, related to cooperative aggregation processes. The morphology of the AHX/CnMIMBr and ALG/CnMIMBr were determined by AFM technique and the size of the aggregates, morphology, topology, hardness, Young's modulus, deformation, adhesion, roughness and electrostatic potential were determined. These studies show that blends of polylelectrolytes with LIs present potential applications in different areas of chemistry, medicine and materials science.